Tunnel Restoration: A Minimally Invasive Dentistry Practice - Nizami MZI; Yeung C; Yin IX; Wong AWY; Chu CH; Yu OY (Dove Medical Press, 2022)
Mohammed Zahedul Islam Nizami, Conson Yeung, Iris Xiaoxue Yin, Amy Wai Yee Wong, Chun Hung Chu, Ollie Yiru Yu Faculty of Dentistry, The University of Hong Kong, Hong Kong Special Administrative Region, People's Republic of ChinaCorrespondence: Ollie Yiru Yu, 3B12 Prince Philip Dental Hospital, Faculty of Dentistry, The University of Hong Kong, 34 Hospital Road, Sai Ying Pun, Hong Kong Special Administrative Region, People's Republic of China, Tel +852 2859 0310, Fax +852 2559 4194, Email ollieyu@hku.hkAbstract: With advances in technology, dentists nowadays manage dental caries with the philosophy of minimally invasive dentistry. Dental restoration is now performed most conservatively with minimal destruction of tooth structure when operative dentistry is indicated. Some operative dentists suggested using tunnel restoration for treating proximal caries as a conservative alternative to the conventional box preparation. The main advantage of tunnel restoration over the conventional box or slot preparation includes being more conservative and increasing tooth integrity and strength by preserving the marginal ridge. However, tunnel restoration is technique sensitive and requires advanced operative skills. Tunnel restoration can be an option to restore proximal caries if the dentist selects the proper case and pays attention to the details of the restorative procedures. With the dentist's advanced training, advanced light-emitting diode handpieces, magnifying loupes, precise digital imaging and new generation restorative materials, good results can be obtained in selected cases. This study reviews the literature on tunnel restoration and provides updated techniques and clinical data that can be used in tunnel restoration to oversee its limitations and the perspective on restorative treatment.Keywords: minimally invasive, tunnel restoration, proximal caries, tunnel preparation, restorative dentistry